(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Serrations, or comb-like structures, have formed along the leading edge of owls’ wings. Serrations were studied from a morphological and mechanical standpoint, but no quantitative comparisons across species were made. Comparative studies of serrations from species with varying sizes and activity patterns may provide fresh insights into the function of serrations. Pigeons and barn owls both have about the same amount of flying feathers, but the barn owls are somewhat bigger. The barn owl’s wing area was much greater than the pigeon’s. The barn owl’s pennula was so lengthy that it often covering the following three or four barbs, whilst the pigeon’s radiates were contained to the region between two barbs.